Automated interpretation of home blood pressure assessment (Hy-Result software) versus physician's assessment: a validation study. Issue 2 (April 2016) - Postel-Vinay, Nicolas; Bobrie, Guillaume; Ruelland, Alan; Oufkir, Majida; Savard, Sebastien; Persu, Alexandre; Katsahian, Sandrine; Plouin, Pierre F.
Abstract : Objective: Hy-Result is the first software for self-interpretation of home blood pressure measurement results, taking into account both the recommended thresholds for normal values and patient characteristics. We compare the software-generated classification with the physician's evaluation. Design method: The primary assessment criterion was whether algorithm classification of the blood pressure (BP) status concurred with the physician's advice (blinded to the software's results) following a consultation ( n =195 patients). Secondary assessment was the reliability of text messages. Results: In the 58 untreated patients, the agreement between classification of the BP status generated by the software and the physician's classification was 87.9%. In the 137 treated patients, the agreement was 91.9%. The κ -test applied for all the patients was 0.81 (95% confidence interval: 0.73–0.89). After correction of errors identified in the algorithm during the study, agreement increased to 95.4% [ κ =0.9 (95% confidence interval: 0.84–0.97)]. For 100% of the patients with comorbidities ( n =46), specific text messages were generated, indicating that a physician might recommend a target BP lower than 135/85 mmHg. Specific text messages were also generated for 100% of the patients for whom global cardiovascular risks markedly exceeded norms. Conclusion: Classification by Hy-Result is at least as accurate as that of a specialist in current practice (http://www.hy-result.com ). Abstract : Supplemental Digital Content is available in the text.